Formulation and Physicochemical Evaluation of Telang Flower (Clitoria ternatea) Extract Lotion as a Skin Moisturizer - Nuraini, April; Naila, Fina (Indonesian Journal of Pharmaceutical Education, 2025)
Dry skin is a common dermatological condition that can adversely affect both comfort and appearance. Natural moisturisers, such as butterfly pea flower (Clitoria ternatea), offer a safe alternative due to their flavonoid and anthocyanin content, which provide antioxidant properties and enhance skin hydration. This study aimed to formulate and evaluate hand and body lotion containing C. ternatea extract and to assess the effect of varying extract concentrations on its physicochemical properties and moisturising efficacy. An experimental study with a quantitative descriptive design was conducted. Three formulations containing 1%, 3%, and 5% extract were prepared using the maceration method with 96% ethanol. Physicochemical evaluations included organoleptic, homogeneity, pH, spreadability, adhesion, and skin moisture tests, with statistical analysis using one-way ANOVA. All formulations met the quality requirements for topical preparations. Significant differences (p 0.05, ANOVA) were observed in pH, adhesion, and moisture, while spreadability showed no significant differences among formulations. The results demonstrate that C. ternatea extract can be successfully incorporated into lotion formulations with effective moisturising properties. Further research should include long-term stability testing, in vivo efficacy and safety assessments, and consumer acceptability evaluations.